A high‐affinity, bivalent PDZ domain inhibitor complexes PICK1 to alleviate neuropathic pain - Nikolaj R Christensen; Marta De Luca; Michael B Lever; Mette Richner; Astrid B Hansen; Gith Noes‐Holt; Kathrine L Jensen; Mette Rathje; Dennis Bo Jensen; Simon Erlendsson; Christian RO Bartling; Ina Ammendrup‐Johnsen; et al. (EMBO Molecular Medicine)
Abstract Maladaptive plasticity involving increased expression of AMPA‐type glutamate receptors is involved in several pathologies, including neuropathic pain, but direct inhibition of AMPARs is associated with side effects. As an alternative, we developed a cell‐permeable, high‐affinity (~2 nM) peptide inhibitor, Tat‐P4‐(C5)2, of the PDZ domain protein PICK1 to interfere with increased AMPAR expression. The affinity is obtained partly from the Tat peptide and partly from the bivalency of the PDZ motif, engaging PDZ domains from two separate PICK1 dimers to form a tetrameric complex. Bivalent Tat‐P4‐(C5)2 disrupts PICK1 interaction with membrane proteins on supported cell membrane sheets and reduce the interaction of AMPARs with PICK1 and AMPA‐receptor surface expression in vivo. Moreover, Tat‐P4‐(C5)2 administration reduces spinal cord transmission and alleviates mechanical hyperalgesia in the spared nerve injury model of neuropathic pain. Taken together, our data reveal Tat‐P4‐(C5)2 as a novel promising lead for neuropathic pain treatment and expand the therapeutic potential of bivalent inhibitors to non‐tandem protein–protein interaction domains.